Comparison of Immigration Laws between Singapore and Indonesia related to Passports (Legal Comparative Study) - Rizka Maulita; Asma Karim (ILAW, 2024)
They are based on the Henley Global Passport Ranking Index; Indonesia's passport is 68th with 76 country visa-free visits. Meanwhile, Singapore's passport is in 1st place with 193 countries' visa-free visits. Singapore has its passport regulations, while Indonesia still has ministerial regulations; with that difference, there's a hypothesis that regulations can affect passport strength. The purpose of this research is to find and analyze the differences between the Singapore Constitution and Indonesia Constitution-related passports and to find and analyze the reasons for the weaknesses of the Indonesia Passport compared to the Singapore Passport. The Author uses juridical normative as the research method. The countries' constitutions are the same, but the weak regulations of Indonesia affect the right of mobility, thus leading to the implication of limited access to certain countries. The five main reasons for Indonesia's weak passport are the number of free-visa visits to countries, diplomatic relations, the country's economy and state welfare, crime rate, and reciprocity factor.